2011
DOI: 10.1200/jco.2010.30.3677
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptor and Progesterone Receptor As Predictive Biomarkers of Response to Endocrine Therapy: A Prospectively Powered Pathology Study in the Tamoxifen and Exemestane Adjuvant Multinational Trial

Abstract: A B S T R A C T PurposeThe Tamoxifen and Exemestane Adjuvant Multinational (TEAM) trial included a prospectively planned pathology substudy testing the predictive value of progesterone receptor (PgR) expression for outcome of estrogen receptor-positive (ER-positive) early breast cancer treated with exemestane versus tamoxifen. Patients and MethodsPathology blocks from 4,781 TEAM patients randomly assigned to exemestane versus tamoxifen followed by exemestane for 5 years of total therapy were collected centrall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
136
3
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(146 citation statements)
references
References 29 publications
6
136
3
1
Order By: Relevance
“…Most studies analyzing predictive or prognostic factors in ER-positive breast cancer have been performed in postmenopausal women, mainly using patients and samples in adjuvant aromatase inhibitor trials [3,4,23]. In premenopausal women, however, even the clinical role of PgR has been little analyzed so far.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies analyzing predictive or prognostic factors in ER-positive breast cancer have been performed in postmenopausal women, mainly using patients and samples in adjuvant aromatase inhibitor trials [3,4,23]. In premenopausal women, however, even the clinical role of PgR has been little analyzed so far.…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen receptor (ER) is essential for estrogen-dependent growth, and its level of expression is considered a crucial determinant of response to endocrine therapy and prognosis in ER-positive breast cancer [1][2][3][4]. On the other hand, the clinical role of progesterone receptor (PgR) in ER-positive breast cancer remains controversial, although testing of PgR by immunohistochemistry (IHC) has become routine [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have investigated tumor biomarkers that indicated differential benefit from aromatase inhibitors versus tamoxifen in patients with early breast cancer (4)(5)(6). Such biomarkers included the conventional factors, estrogen receptor (ER), progesterone receptor (PgR), human epidermal growth factor receptor type 2 (HER2) and Ki-67, and did not identify patients who derived a differential relative benefit from aromatase inhibitors over tamoxifen.…”
Section: Introductionmentioning
confidence: 99%
“…We agree that different treatment may account for different outcome, as shown in the study by Bartlett et al 5 For survival analysis, they used TEAM (Tamoxifen vs Exemestane adjuvant Multicentre) pathology study composed of estrogen receptor-positive early breast cancers, treated with adjuvant endocrine therapy (exemestane versus tamoxifen), but not with chemotherapy. 6 However, tumors with heterogeneous HER2 amplification cannot be equated with those with borderline/low HER2 amplification. Although HER2 genetic and regional heterogeneity was more common in tumors with equivocal/low-grade amplification, they were found in 23 and 38% of tumors with equivocal/lowgrade amplification in our study.…”
mentioning
confidence: 99%